Anxiety and psychosomatic symptoms in palliative care: from neuro-psychobiological response to stress, to symptoms’ management with clinical hypnosis and meditative states - Satsangi, Anirudh Kumar; Brugnoli, Maria Paola (Annals of Palliative Medicine; Vol 7, No 1 (January 26, 2018): Annals of Palliative Medicine (Clinical Hypnosis in Palliative Care: neural correlates, clinical, psychological and spiritual therapies), 2018)
Psychosomatic disorder is a condition in which psychological stresses adversely affect physiological (somatic) functioning to the point of distress. It is a condition of dysfunction or structural damage in physical organs through inappropriate activation of the involuntary nervous system and the biochemical response. In this framework, this review will consider anxiety disorders, from the perspective of the psychobiological mechanisms of vulnerability to extreme stress in severe chronic illnesses. Psychosomatic medicine is a field of behavioral medicine and a part of the practice of consultation-liaison psychiatry. Psychosomatic medicine in palliative care, integrates interdisciplinary evaluation and management involving diverse clinical specialties including psychiatry, psychology, neurology, internal medicine, allergy, dermatology, psychoneuroimmunology, psychosocial oncology and spiritual care. Clinical conditions where psychological processes act as a major factor affecting medical outcomes are areas where psychosomatic medicine has competence. Thus, the psychosomatic symptom develops as a physiological connected of an emotional state. In a state of rage or fear, for example, the stressed person’s blood pressure is likely to be elevated and his pulse and respiratory rate to be increased. When the fear passes, the heightened physiologic processes usually subside. If the person has a persistent fear (chronic anxiety), however, which he is unable to express overtly, the emotional state remains unchanged, though unexpressed in the overt behavior, and the physiological symptoms associated with the anxiety state persist. This paper wants highlight how clinical hypnosis and meditative states can be important psychosocial and spiritual care, for the symptom management on neuro-psychobiological response to stress.